Ancient Prophecy Near Eastern, Biblical, and Greek Perspectives - Nissinen, Martti (Oxford University Press, 2017)
This book is a comprehensive treatment of the ancient prophetic phenomenon as it comes to us through biblical, Near Eastern, and Greek sources. Once a distinctly biblical concept, prophecy is today acknowledged as yet another form of divination and a phenomenon that can be found all over the ancient Eastern Mediterranean. Even Greek oracle, traditionally discussed separately from biblical and Mesopotamian prophecy, is essentially part of the same picture. The book gives an up-to-date presentation of textual sources, whether cuneiform tablets from Mesopotamia, the Hebrew Bible, Greek inscriptions, or ancient historians, the number of which has increased substantially in recent times. In addition, the book includes comparative essays on topics such as prophetic ecstasy; temples as venues of prophetic performances; prophets and political rulers; and the prophets' gender which can be either male, female, or non-gendered. The book argues for a common category of ancient Eastern Mediterranean prophecy, even though the fragmentary and secondary nature of the sources allows only a restricted view to it. The ways prophetic divination manifests itself in ancient sources depend not only on the socio-religious position of the prophets but also on the genre and purpose of the sources. The book shows that, even though the view of the ancient prophetic landscape is restricted by the fragmentary and secondary nature of the sources, it is possible to reconstruct essential features of prophetic divination.